Can young children's nutritional needs be met with a combination of fortified blended foods and local foods? - Ruel, Marie T.; Loechl, Cornelia U.; Menon, Purnima; Pelto, Gretel H. (International Food Policy Research Institute, 2004)
Fortified donated cereal blends can greatly contribute to improving the nutritional quality of complementary foods, but are not sufficient to completely close the iron and zinc gaps at current fortification levels in Haiti, even when combined with locally available foods. -- from Text